Karma Yoga and Human Responsibility in Vivekananda’s Thought - Ghosh, Kanchan (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
This study critiques Swami Vivekananda’s Karma Yoga philosophy and ethics, focusing on its effects on human responsibility. I propose that Vivekananda’s Karma Yoga redefines obligation by integrating selflessness, non-attachment, and moral awareness into ethical action, linking personal growth with social responsibility. I believe that doing one’s responsibility without attachment to results promotes inner freedom and ethical accountability. I analyse Vivekananda’s writings, including The Complete Works of Swami Vivekananda, to show how moral causation, equanimity in success and failure, and service-oriented action form a coherent model of responsible human agency. Karma Yoga is still relevant in organizational ethics, leadership, and environmental stewardship, where ego, attachment, and short-termism often impair ethical conduct, according to the study. Vivekananda’s ideas emphasize that human responsibility is transformational and relational, providing a solid framework for moral consciousness and practical participation. This paper reinterprets Karma Yoga as a lived philosophy to contribute to ethics, moral psychology, and applied philosophy discussions and highlight the continuing importance of Indian philosophical traditions in addressing ethical action, personal development, and collective well-being.